RNALocate v2.0: an updated resource for RNA subcellular localization with increased coverage and annotation. Issue Volume 50:Issue D1(2022) (22nd September 2021) - Cui, Tianyu; Dou, Yiying; Tan, Puwen; Ni, Zhen; Liu, Tianyuan; Wang, DuoLin; Huang, Yan; Cai, Kaican; Zhao, Xiaoyang; Xu, Dong; Lin, Hao; Wang, Dong
Abstract: Resolving the spatial distribution of the transcriptome at a subcellular level can increase our understanding of biology and diseases. To facilitate studies of biological functions and molecular mechanisms in the transcriptome, we updated RNALocate, a resource for RNA subcellular localization analysis that is freely accessible at http://www.rnalocate.org/ or http://www.rna-society.org/rnalocate/ . Compared to RNALocate v1.0, the new features in version 2.0 include (i) expansion of the data sources and the coverage of species; (ii) incorporation and integration of RNA-seq datasets containing information about subcellular localization; (iii) addition and reorganization of RNA information (RNA subcellular localization conditions and descriptive figures for method, RNA homology information, RNA interaction and ncRNA disease information) and (iv) three additional prediction tools: DM3Loc, iLoc-lncRNA and iLoc-mRNA. Overall, RNALocate v2.0 provides a comprehensive RNA subcellular localization resource for researchers to deconvolute the highly complex architecture of the cell.